A novel color-LED corneal topographer to assess astigmatism in pseudophakic eyes - Ferreira TB (Dove Medical Press, 2016)
Tiago B Ferreira, Filomena J Ribeiro Department of Ophthalmology, Hospital da Luz, Lisbon, Portugal Purpose: To assess the accuracy of corneal astigmatism evaluation measured by four techniques, Orbscan IIz®, Lenstar LS900®, Cassini®, and Total Cassini (anterior + posterior surface), in pseudophakic eyes. Patients and methods: A total of 30 patients (46 eyes) who had undergone cataract surgery with the implantation of a monofocal intraocular lens (AcrySof IQ) were assessed after surgery. For each eye, subjective assessment of astigmatism and its axis was performed. Minimum, maximum, and mean keratometry and astigmatism and its axis were evaluated using the four measurement techniques. All measurements were compared with the subjective measurements. Agreement between each measurement technique and subjective assessment was evaluated using Bland–Altman plots. Linear regressions were performed and compared. Results: Linear regression analysis of astigmatism axis showed very high R2 for all models, with Total Cassini showing the least difference to the unit slope (0.052) and the least difference to a null constant (3.790), although not statistically different from the other models. Regarding astigmatism value, the Cassini and Total Cassini models were similar and statistically better than the Lenstar model. Cassini and Total Cassini showed better J0 compared with Orbscan. Conclusion: On linear regression models, Cassini and Total Cassini showed the best performance regarding astigmatism value. Cassini and Total Cassini also showed the least J0 deviation from the Cartesian origin compared with Orbscan, which had the lowest performance. Total corneal measurement with the color LED topographer seems to be a better technique for astigmatism assessment. Keywords: astigmatism, keratometry, topography